Maternal late-pregnancy serum 25-hydroxyvitamin D in relation to childhood wheeze and atopic outcomes - Pike, K; Pike, K; Inskip, H; Inskip, H; Robinson, S; Robinson, S; Lucas, J; Lucas, J; Cooper, C; Cooper, C; Cooper, C; Harvey, N; et al. (2012)
Background: Studies exploring the relationship between prenatal vitamin D exposure and childhood asthma have yielded conflicting results. Higher vitamin D intake during pregnancy has been shown to lower the risk of childhood wheeze, yet a study of maternal late-pregnancy serum 25-hydroxyvitamin D suggested higher serum concentrations may be associated with increased childhood asthma. Objective: To assess the relationship between mothers' serum 25-hydroxyvitamin D status and asthma and wheeze phenotypes in their children at age 6 years. Also to explore the relationship between maternal 25-hydroxyvitamin D status and objective measures of childhood atopy and lung function. Methods: Serum 25-hydroxyvitamin D was measured at 34 weeks' gestation in the mothers of 860 children born at term. Wheeze was classified as either transient or persistent/late using questionnaire data collated from 6, 12, 24 and 36 months and 6 years. At 6 years spirometry was performed and atopic status was determined by skin prick testing, exhaled nitric oxide was measured in 451 children and bronchial hyperresponsiveness in 216 children. Results: There were no significant associations between maternal late-pregnancy 25-hydroxyvitamin D status and either asthma or wheeze at age 6 years. Maternal vitamin D status was not associated with transient or persistent/late wheeze; no significant association was found between persistent/late wheeze when subdivided according to atopic status. No associations were found with skin sensitisation or lung function. Conclusions: This study provides no evidence that exposure to higher concentrations of 25-hydroxyvitamin D in maternal serum during late pregnancy increases the risk of childhood asthma, wheeze or atopy.